Effects of ocean acidification on the behaviour and anaesthesia of juvenile Abudefduf troschelii (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Ocean acidification (OA) may affect the structure, physiology, and behavior of several marine taxa, particularly during early developmental stages. We evaluated the effects of OA on physiological and ethological parameters in juveniles of the pomacentrid Abudefduf troschelii through anesthesia and behavioral tests. Behavioral test results, analyzed by groups, showed no significant changes associated with reduced seawater pH. Regarding physiological responses, no significant differences were observed during the induction and general anesthesia phases; however, recovery time was significantly longer in organisms exposed to OA conditions. Overall, the results suggest that conditions associated with ocean acidification affect juveniles of A. troschelii exposed to short periods of hypercapnia, which, although not detectable through behavioral analyses, may be revealed through physiological response assessments.